Site investigation on Sg. Belat bridge and road approaching KM1 federal road FR012 Jalan Gambang-Muadzam Shah, Pahang - Nur Wahidah, Kamaruddin (2012)
Road accident is one of an attractive issue to be focused seriously. The reason is because road accident is the main cause of the death in Malaysia. According to statistic from the Malaysia Road Safety Council the death toll were 5672 in 2007, 5952 in 2008, 6218 in 2009 and 6260 in 2010 and 6350 peoples in 2011. The total death of the past 5 years is 30 342 peoples. The number of accident still very high in Malaysia despite various intervention programmed is handle by the authority in reducing the number of accident. The purpose of this case study are to find out the visibility defect from point of view of geometric design that contributes to the accidents occurrences and to propose an innovative road design and infrastructure solution to improve the safety standard for road design. This study was carried out by site investigation to detect all the road and infrastructures deficiencies alaong the study location. The location of this study is on KM 1, Federal Road FR012 Jalan Gambang- Muadzam Shah, in Pahang. The result of this study indicates that the road design and infrastructures deficiencies are one of the major factorS that can bring hazard to road users and contributes road accidents.